The effects of Co and Cr particles additions on microstructure and wear behaviour of Pb-Sn based alloy - Teker, Tanju; Kaplan, Mehmet (Elsevier Science Sa, 2009)
In this study a Pb-Sn based alloy has been produced by adding Co and Cr particulate by means of mechanical processes. The effects of Co and Cr particles additions on the abrasive wear behaviours; of Pb-Sn alloy were investigated by using a pin-on-disc wear tester. Wear tests were performed under constant rotational speed and variable loads. The weight loss was measured by using a precise balance with accuracy of 10(-4) g at room temperature. Worn surface mechanism, changes of the microstructure, mechanical and phase characteristics of the specimens were examined by using scanning electron microscopy, electron diffraction spectrometer, X-ray diffraction and hardness measurement techniques. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Pb-Sn alloy; Wear test; Microstructure